Creencias irracionales y autoconcepto en personas con discapacidad motora adquirida, del centro comunitario Capodarco, cantón Penipe, provincia de Chimborazo’’ - Benalcázar Mancero., María Francisca (2017)
This research project was developed in the Capodarco community, in Penipe city, with a sample of 15 members, with the purpose of analyzing irrational beliefs and self-concept in people with physical disabilities. The presence of irrational beliefs and the level in each sphere of self-concept of the participants were determined. The research design is of quantitative type, with descriptive, non-experimental cross-sectional scope. The psychological batteries used are the "Autoconcept Form 5 Scale" - AF5 (2014) and the "Albert Ellis Opinions Record" (2015), which gave as a result: There is pathology in 7 of the 10 irrational ideas, (1) (To be human it is imperative to be loved or accepted by any other relevant member of the circle) and 9 (A past event is a decisive determinant of present behavior, because if something affected us greatly once in a lifetime, then it will continue to disturb us indefinitely) in the same percentages 26.7%. In addition, low self-concept is identified among the spheres: emotional 60.0%, physical 26.7%, familial 13.3%, and social 6.7%, without being problematic at an academic level.. The correlation of the variables with the Tau_de_Kendall test established a non-significant relationship in all the correlation tests, being made between variables and factors such as: age, gender, schooling and disability temporality. The study concluded that there is no correlation between irrational beliefs and self-concept.